Concerning suicide in Croatia: who, when, where and how - Lugomer Armano, Goranka; Frlan, Ana; Maričić, Jelena Subotić, Sanja (2006)
Croatia is passing through a turbulent social and economic transition. Problems of PTSD among war veterans, unemployment, low income, high rate of divorce, increase of violence in family, school and job settings - are background for an increase in alcoholism and depression which in connection with easy assessable fire-arms can lead to an increase of suicide. However, the suicide rate in Croatia seems to be stable – about 20. The aim of this study is to give an overview of subjects - professionals, institutions, data basis, bibliographic references and media resources which have dealt with the issue of suicide in Croatia during the last decades. Objectives were: 1. to find out and compare the resources and kind of data collected about suicides and suicide attempts and to offer epidemiographic overview of their socio-demographic and contextual correlates ; 2. to list out the bibliography on suicide published in Croatia and to make their content analyses by using six categories analogue to six issue areas of the congress ; 3. to view the treatment of suicide in Croatian media ; 4. to review the treatments of suicide attempters and the suicide prevention programs and 5. to offer the developmental schedule for establishing National strategy of suicide prevention.
Projekt MZOS
ENG